(3eMGSHI GdfaW (B/s - (3YHO Gddg, NGdO Cejfs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2001)
(3NUGFU eMGSHI GdfaW, GdOdjd GdeMGSHj aj TQcGJ GfJGL GdfaW, eUQhaGJ GdESJcTGa hGdMUhd Ydi GdYbhO GdEeJjGR, GdCdGJ h GdeYOGJ, GdEgdGc aj TQcGJ GfJGL GdfaW , WHjYI GdCUhd GdeJfGbUI hNUGFUgG, faGP GdeeJdcGJ GdefJLI, GdYbhO ZjQ GdeWhQI, eUGQHa GdMaQ hEYOGO HFQ GdEfJGL, JcdaI eQGMd GdEfJGL, GdJcGdja GdeTJQcI aj UfGYI GdfaW, JUhjQ fJjLI GdfTGW hHjGf GdeQcR GdeGdjs
Keywords: (3GdHJQhds; (3eMGSHI(B- (3GdTQcGJs